Technological and Institutional Innovations for Marginalized Smallholders in Agricultural Development (2016)
We face a global food crisis of many dimensions. Food prices for the poor are rising and volatile. About a billion people are chronically hungry. Most shocking of all, 1 in 3 children under the age of five are seriously malnourished and will grow up physically and mentally stunted. At the same time, some two billion people are overweight or obese. Furthermore, we have to feed a growing world population demanding more varied and nutritious diets, including a wide range of livestock products. We will have to produce more food, but on more or less the same amount of land and with the same amount of water. In recent years, I and a team of experts drawn from Europe and Africa, known as the Montpellier Panel, have been attempting to articulate the concepts, frameworks and practical actions we will need to cope with these challenges. We have argued that a way forward is sustainable intensification, producing more with less, but also using inputs more prudently, adapting to climate change, reducing greenhouse gases, improving natural capital and building resilience. It is a tall order, a chal- lenge far greater than that we faced at the time of the Green Revolution. An important contribution to the debate is this volume edited by Franz Gatzweiler and Joachim von Braun. Its aim is to improve the understanding of how, when and why innovation can bring about sustainable intensification in agriculture, improving the lives of poor smallholders, a majority of which live in Sub-Saharan Africa and South Asia. It presents contributions from theory, policy and practice to the science of sustainable intensification. The volume explores opportunities for marginalized smallholders to make use of technological and institutional innovations in order to achieve sustainable intensification and improve productivity and wellbeing.